Takeover vulnerability and the behavior of short-term stock returns - Chae, Joon; Lee, Dong Wook; Wang, Shu Feng (Journal of Corporate Finance, 2013)
This paper proposes and tests the hypothesis that takeover vulnerability contributes to short-term price reversal by motivating investors to trade speculatively and also by making investors demand immediacy in their trades. That is, takeover vulnerability is hypothesized to amplify two channels of short-term price reversal, namely, overreaction and price concession. Using several different measures of takeover vulnerability, we find that takeover vulnerability is positively related to price reversal at daily frequencies. We also find that their positive relation is more pronounced when the stock is illiquid or when it is costly to arbitrage, a finding that is consistent with the notion that the observed price reversal is driven by the earlier price concession or overreaction. While unable to determine the exact relative importance between the two channels, we conduct further analysis showing that each channel plays an independent role. Finally, we find no relation between takeover vulnerability and price reversal at the portfolio level, which means that the price reversal observed in individual stock returns is driven by a firm-specific component.